2015
DOI: 10.1007/s10911-015-9333-4
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on COX-2 in Chronic Inflammation Driving Breast Cancer Growth and Metastasis

Abstract: The medicinal use of aspirin stretches back to ancient times, before it was manufactured in its pure form in the late 19th century. Its accepted mechanistic target, cyclooxygenase (COX), was discovered in the 1970s and since this landmark discovery, the therapeutic application of aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) has increased dramatically. The most significant benefits of NSAIDs are in conditions involving chronic inflammation (CI). Given the recognized role of CI in cancer deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 139 publications
(158 reference statements)
2
75
0
Order By: Relevance
“…The potential role of inflammation in driving high mammographic density suggests that use of non-steroidal anti-inflammatory drugs (NSAID), which are already known to reduce breast cancer risk [63, 64], could be effective in reducing mammographic density. In a mouse model of HMD, Celecoxib, a selective NSAID that specifically inhibits COX2, was shown to reduce collagen deposition in the mammary gland, and reduce tumour development and metastasis [65].…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of inflammation in driving high mammographic density suggests that use of non-steroidal anti-inflammatory drugs (NSAID), which are already known to reduce breast cancer risk [63, 64], could be effective in reducing mammographic density. In a mouse model of HMD, Celecoxib, a selective NSAID that specifically inhibits COX2, was shown to reduce collagen deposition in the mammary gland, and reduce tumour development and metastasis [65].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and post-partum involution are chronic inflammatory states in mammary glands, and are associated with increased breast cancer risk (3). Furthermore, non-steroidal anti-inflammatory drugs (NSAID), which are nonselective Prostaglandin G/H synthase 2, or cyclooxygenase-2 (COX-2) inhibitors, significantly reduce the risk of mammary carcinogenesis, recurrence, and motility of breast cancer (4).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis of 90 studies conducted by Harris (16) indicated that regular administration of selective COX-2 inhibitors significantly reduced the incidence of colon, breast, lung and prostatic cancer. As breast cancer has been studied more extensively in recent years, the effects of COX-2 have been increasingly highlighted (17,18). Animal experiments have demonstrated that the overexpression of COX-2 induced the genesis of breast cancer in transgenic mice (19).…”
Section: Introductionmentioning
confidence: 99%